Phosphorus Composition of Sheep Feces and Changes in the Field Determined by 31P NMR Spectroscopy and XRPD - Shand, Charles A; Coutts, Grace; Hillier, Stephen; Lumsdon, David G; Chudek, Alexander; Eubeler, Jan (Environmental science & technology, 2005)
Information on the P species in sheep feces is lacking. Such information is required to understand P-cycling in grazed ecosystems. The P composition of feces from sheep grazing grass in Scotland was assessed on freeze-dried samples by 31P MAS (magic angle spinning) NMR (nuclear magnetic resonance) spectroscopy and XRPD (X-ray powder diffraction). The 31P MAS NMR spectrum showed resonances and sidebands consistent with dicalcium phosphate dihydrate (brushite) and ammonium magnesium phosphate hexahydrate (struvite). XRPD confirmed the result and allowed quantification of these minerals, which accounted for 63% of the P. To determine transformations in the field, sheep feces were collected and reapplied to sheep-free pasture in synthetic patches during late summer. The dry weight decreased with time and the feces disappeared between 84 and 112 days following heavy rainfall. The concentration of P in the feces recovered at intervals up to 84 days changed little with time but the contribution from brushite and struvite decreased and within 1 week <50% remained indicating conversion into other forms. Solution-phase 31P NMR spectra of NaOH/EDTA extracts of the feces were dominated by the inorganic orthophosphate with minor amounts of organic P that were attributed to phosphate esters and polyphosphates.